ZAKAT PRODUCTIVE AND POVERTY REDUCTION - Bachrul Ulum (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTThis study aims to examine productive zakat and poverty alleviation. The research uses a qualitative approach with the type of library research. The results show that there are three steps or strategies that can be taken together to build a system that is able to support the development of economic independence with zakat as one of the main pillars, namely as follows: 1) free financial access is an effort to reduce poverty by suppressing proverty. Unemployment number; 2) zakat management needs to apply the principle of profit and loss sharing (PLS) standardly for all economic activities; 3) optimize zakat and make it an investment savety net. Zakat has a very strategic contribution in efforts to reduce poverty or improve economic levels. In contrast to other financial sources, zakat does not have any reciprocal impact except expecting the pleasure and reward of Allah SWT alone.Keywords: Productive Zakat, Poverty